BAOXIN Granules Protected Mouse Model With Elevated Afterload From Cardiac Hypertrophy by Suppressing Both Inflammatory Reaction and Collagen Deposition - Qiu, Xu; Ma, Ji; Shi, Yujing; Zhang, Dong; Li, Defeng; Dong, Zhao; Lin, Xiao; Shi, Haozhe; Jiang, Guining; Wang, Yuhui; Liu, George (Frontiers in Physiology, 2019)
Baoxin Pill was reported to be effective clinically for chronic heart failure based on the principles of Traditional Chinese Medicine (TCM), invigorating qi and activating blood. The present study evaluated preclinically the effects of the improved dosage form, Baoxin Granules, on cardiac hypertrophy. Transverse aortic constriction (TAC) was performed in mice to model cardiac hypertrophy by aortic stenosis for 4 weeks. The sham and TAC group were intragastrically administrated with saline as the controls. Two treatment groups were administrated orally with 10mg/kg•d Enalapril (positive control) or 0.77g/kg•d Baoxin Granules for 4 weeks respectively. The effects were evaluated by echocardiography, morphology and biological markers for cardiac function. The specific genes involved in inflammation and fibrosis were also examined for their expressions to investigate the pathways involved in early heart failure. Just as Enalapril, Baoxin Granules administration markedly attenuated left ventricular hypertrophy and improved heart function as evidenced by echo cardiography, morphology. Accordingly, the biomarkers of the early stage heart failure, ANP, BNP and β-MHC, were decreased in the two treatment groups. We also found that mRNA expressions of some inflammatory factors and fibrosis associated genes were down-regulated in the tissue of heart after treatment. Baoxin Granules may protect the heart from myocardial hypertrophy caused by increasing left ventricular afterload. It can suppress both inflammatory reaction and collagen deposition during pressure overload. Baoxin Granules is advised to be tested in clinical trials for heart failure in the future.